Hereditary Medullary Thyroid Cancer: Age-Appropriate Thyroidectomy Improves Disease-Free Survival - Shepet, Kevin (2012)
BACKGROUND: Twenty-five percent of Medullary Thyroid Cancer (MTC) cases are hereditary. The ideal age for prophylactic thyroidectomy is based upon the specific RET mutation involved. The aim of this study is to determine if such age-appropriate prophylactic thyroidectomy results in improved disease-free survival. METHODS: Twenty-eight patients underwent thyroidectomy for hereditary MTC at our institution. Age-appropriate thyroidectomy was defined according to the North American Neuroendocrine Tumor Society (NANETS) guidelines. Patients having age-appropriate surgery (Group 1, n=9) were compared to those having thyroidectomy past the recommended age (Group 2, n=19). RESULTS: The mean age was 13 ± 2 years and 61% were female. Patients in Group 1 were younger than Group 2 (4 ± 1 vs. 17 ± 2 years, p<0.01). There were no significant differences in gender or RET mutation types between these two groups. Group 1 patients were cured with no disease recurrence as compared to Group 2 patients who had a 42% recurrence rate (p=0.05). Sub-analysis of Group 2 identified that patients who underwent surgery without evidence of disease did so at a shorter period following the guidelines as compared to those who underwent therapeutic surgery (2 ± 2 vs. 16 ± 2 years, p=0.01) and had longer disease-free survival (100% vs. 27%, p=0.005). CONCLUSION: Patients with hereditary MTC should undergo age-appropriate thyroidectomy based on RET mutational status to avoid recurrence. Patients who are past the recommended age should have surgery as early as possible in order to improve disease-free survival.